Pulsando el cambio, propuesta a un nuevo paradigma : economía alternativa. - Bravo Álvarez, Sofía Katherine (2018)
One of the most urgent debates that has been brought by the turn of the century — with its social, environmental, political, economic and cultural peculiarities — for societies and social sciences, examines pathways to overcome the so-called civilizational crisis. That is, a set of global conditions that directly influences humans’ daily life and involve the following: a) the environmental and ecological crisis, which implies the degradation of life as we know it; b) the economic and social crisis, which causes inequality and the exploitation of most human beings; c) the political models that sustain and favour these dynamics on a global scale; d) a culture based on consumption and waste, which controls the psychology and habits of Western societies at the expense of nature and the common good of living beings. This paper, thus, critically reviews available literature on the aforesaid subject. In addition, it exposes proposals and reflections aimed at overcoming the current civilizational crisis. Three authors and their works are taken as the main sources for the review, namely: Charles Einsenstein (The Sacred Economy, 2011); Euclides Mance (The revolution of the networks, 2006) and Christian Felber (Economy of the Common Good, 2010). All three propose alternative models and substitutes to the prevailing capitalistic hegemonic model, which emerge from economy, historical interpretation, social, political and economic systems, philosophy and other tools of the social science.